(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
White Mango Scale (WMS), Aulacaspis tubercularis Newstead (Hemiptera: Diaspididae), was occurred in Ethiopia in 2010. It was introduced from Asia (India) through infected mango seedlings. Currently the insect problems increase to different parts of Ethiopia. This survey was initiated with the objectives of gathering perception of mango growing farmers on mango WMS insect status and its management methods. Semi-structured questionnaires were administered to mango growing farmers selected at random with majority being members of the banana and mango producers. Survey result shows that white mango scale insect is present at all the studied area and all the interviewed farmers responded that their mango tree was faced with some sort of insect problem and some farmers started to manage this insect by cultural and chemical methods. From the interviewed mango growers, 57.3% were knowledge on white mango scale insect and they thought it causes high amount of yield loss. Sixty percent of the respondents use one or combination of control methods of the pest. Further systematic study is needed to implement informed management system to control this emerging mango pest.